National Pretrial Reporting Program, 1990-1991 ([Verlag nicht ermittelbar], 1993)
This data collection effort was undertaken to determine whether accurate and comprehensive pretrial data can be collected at the local level and subsequently aggregated at the state and federal levels. The data contained in this collection provide a picture of felony defendants' movements through the criminal courts. Offenses were recoded into 14 broad categories that conform to the Bureau of Justice Statistics' crime definitions. Other variables include sex, race, age, prior record, relationship to criminal justice system at the time of the offense, pretrial release, detention decisions, court appearances, pretrial rearrest, adjudication, and sentencing. The unit of analysis is the defendant.